Pertumbuhan Ikan Komet (Carassius auratus) pada Sistem Vertiqua dengan Menggunakan Biofikal Filter - Iqbal Said Nawawi, Muhamad; Ujang Dindin; Novita MZ (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
The growth of comet fish (Carassius auratus) in the vertiqua system using a biofical filter is motivated by limited land and water which can cause low water quality to affect the growth rate of fish. The utilization of technology needs to be done to overcome these problems and the technology used is vertiqua. Previous research showed that comet fish in the vertiqua system produced slow growth rates and had high ammonia levels. Therefore, vertiqua was modified in the filter section to become a biofical filter. The purpose of this research is to test the effectiveness of comet fish growth in the vertiqua system using a biofical filter. The benefits of this research are that the vertiqua system using a biofical filter can be a solution to overcome the problem of limited land and water, become a support for system cultivation innovation, and become a reference for further research. This research method uses descriptive methods, observation and interviews. The comet fish used in the study were 3-4 cm in size. The results of this study indicate that the vertiqua system using a biofical filter is still not effective in supporting fish growth. The growth rate of comet fish in the vertiqua system is significantly different from that in the soil pond and the growth rate of comet fish in the vertiqua system is lower than that of comet fish in the soil pond. Ammonia value is relatively high from the quality standard (>0.05). However, this system is able to maintain good fish survival and good water quality, especially in temperature, pH, and DO.